Llama Llama back to school - Dewdney, Anna; Duncan, Reed (Llama Llama., 2022)
"Summer days are getting shorter and it's almost time for the first day of school for Llama! But Llama Llama isn't ready for summertime to end. It's been full of backyard camping, family picnics, and ice cream with friends. All he wants is for summer to go on forever! He's anxious about his first day back at school but maybe, with some help from his friends and Mama Llama, going back to school will be fun after all."--